How are the characteristics of Indonesian Muslim Tourists on Muslim Friendly Services in non-Muslim destination - Pranindyasari, Chelsia; Wibawa, Berto Mulia; Gultom, Liza Khairunnisa (Journal of Halal Research, Policy, and Industry, 2022)
The increasing number of Muslim world tourists creates a big opportunity for the halal tourism market. With the largest Muslim population in the world, Indonesia has the potential to develop halal tourism services. Meanwhile, Muslim tourists more often visit non-Muslim-majority countries that do not understand the need for halal tourism. This research was conducted with the aim of identifying the dominant characteristics of Indonesian Muslim tourists when visiting non-Muslim majority countries. The research design is descriptive cross sectional and uses a purposive sampling technique. 268 samples were obtained from online questionnaires and analyzed using descriptive mapping. There are two findings in this study, the characteristics of preparation before travelling to non-Muslim countries and when they travel to non-Muslim countries. Managerial implications can be used as the basis for marketing strategies by tourism organizations in non-Muslim countries and tourism service providers to offer based on Muslim needs.